2010
DOI: 10.1088/0953-8984/22/22/225501
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the electronic and magnetic structures of P-doped graphene by molecule doping

Abstract: The adsorption of gas molecules on P-doped graphene (PG) was theoretically studied using density-functional theory in order to find the possibility of modulating electronic and magnetic ordering of graphene. H₂, H₂O, CO₂, CO, N₂ and NH₃ molecules are physisorbed, while NO, NO₂, SO₂ and O₂ molecules are strongly chemisorbed on PG through the formation of P-X (X = O, N, S) bonds. P dopant introduces global spin polarization into graphene with order of 1.05 μ(B). Chemisorption of NO₂ and SO₂ makes the spin polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
87
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 34 publications
7
87
0
Order By: Relevance
“…For example, we found that a band gap of 0.30 eV could be opened when a sulfur atom replaces a carbon atom in a 5 Â 5 graphene supercell [12], whereas a larger band gap was determined for P-doped graphene, even though Al-doped graphene is metallic [13]. The Pdoped and S-doped graphenes have outstanding properties to construct sensors for NO 2 and SO 2 [6,7]. However, Al-doped graphene is not expected to be a good candidate because it is too reactive.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, we found that a band gap of 0.30 eV could be opened when a sulfur atom replaces a carbon atom in a 5 Â 5 graphene supercell [12], whereas a larger band gap was determined for P-doped graphene, even though Al-doped graphene is metallic [13]. The Pdoped and S-doped graphenes have outstanding properties to construct sensors for NO 2 and SO 2 [6,7]. However, Al-doped graphene is not expected to be a good candidate because it is too reactive.…”
Section: Introductionmentioning
confidence: 95%
“…This can be attained by electrochemical reaction with ammonia [3], chemical vapor deposition [4] or simultaneous Ndoping and reduction of graphene oxide [5]. In second place, the applications are largely motivated by the theoretic investigations [6][7][8][9][10][11][12][13] guiding in the identification of the materials whose synthesis would be easier and also unraveling the chemical properties of the new carbon based nanostructures that can be used in nanodevices. Recent publications showed that using sulfur or phosphorus atoms [6][7][8]12,13] it is possible to open a band gap in the band structure of graphene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the synthesis of graphene doped with 3 p elements has proven to be more taxing. For example, if Al is used as the dopant, strong structural changes are induced, because Al has an atomic radii that is considerably larger than that of C. [10][11][12][13][14][15] However, despite the larger radii of Si, P, and S, the preparation of Si-doped, [14][15][16][17][18][19] P-doped, [14,15,[20][21][22][23][24][25] and S-doped [14][15][25][26][27][28][29][30][31][32][33] graphene has been reported. The new materials have been characterized by means of theoretical and experimental techniques.…”
Section: Introductionmentioning
confidence: 99%
“…17,[22][23][24][25][26][27][28] For example, the band of bilayer graphene is opened when K atoms are adsorbed on grapheneSiC system. 24 This is due to that the SiC acts as hole doping and K atom acts as electron doping.…”
mentioning
confidence: 99%